HUBUNGAN TINGKAT PENGETAHUAN IBU NIFAS TENTANG KOLOSTRUM DENGAN MOTIVASI PEMBERIAN KOLOSTRUM DI DESA SIDOREJO KECAMATAN SERAPIT KABUPATEN LANGKAT TAHUN 2019 - ELISABETH BR SINGARIMBUN (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Colostrum, namely breast milk (ASI), which is produced on the first day until the third day after the baby is born, has a slightly yellowish yellow color than ordinary breast milk, is rather rough because it contains fat droplets. Colostrum is a part of breast milk that is very, very important to be given in the first life of a baby because colostrum contains immune substances, especially immunoglobulin (IgA) to protect babies from various infectious diseases. Colostrum has properties to clean meconium so that the intestinal mucosa of a newborn baby is immediately clean and ready to receive breast milk. The design in this study uses cross sectional. This study aims to determine the relationship of postpartum knowledge about colostrum with the motivation of giving colostrum in Sidorejo Village, Serapit Subdistrict, Langkat Regency in 2019. The sample in this study was 30 respondents. The results of this study are based on the results of the calculation of non-parametric statistical tests that use the Chi Square test correlation obtained p-value of 0.024 <0.05. This means that Ha was accepted and Ho was rejected, so it can be concluded that there was a significant relationship between the Postpartum Mother's Knowledge Level about Colostrum and the Motivation of Colostrum Giving in Sidorejo Village, Serapit District, Langkat Regency.